Image-Guided Percutaneous Spine Biopsy - Ortiz, A. Orlando; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook covers key areas and reviews important principles and steps in the preparation for and the performance of spine biopsy. Image-guided percutaneous biopsy techniques and their application throughout the spinal axis are presented and discussed in detail. The advantages and disadvantages of various spine biopsy instruments are reviewed. Commonly encountered biopsy scenarios are considered in order to help readers effectively manage these situations when they occur in their practices. Clear guidance is offered on patient selection and preparation, which are critical to safe and effective outcomes, and much emphasis is placed on procedural safety, with a focus on complication avoidance and the appropriate reporting of complications. Image-Guided Percutaneous Spine Biopsy will be a welcome one-stop shop providing up-to-date information for all physicians with an interest in the subject, including radiologists, surgeons, and pathologists.
Patient selection/preparation -- Coagulation, Anti-coagulation and spine biopsy -- Sacral biopsy technique -- Lumbar spine biopsy techniques -- Thoracic spine biopsy techniques -- Cervical spine biopsy techniques -- Spine infection -- Spine infection mimics -- Post-op spine biopsy -- Paraspinal soft tissue biopsy -- Pathologic considerations in spine biopsy -- Open biopsy.
Keywords: Medicine; Interventional radiology; Pathology; Surgery; Medicine & Public Health; Interventional radiology; Surgery; Pathology